Improved performance and reproducibility of perovskite solar cells by jointly tuning the hole transport layer and the perovskite layer deposition - Sharma, Ashish; Rath, Arup K. (Journal of Materials Science Materials in Electronics, 2018)
Solution processed organometal trihalide materials spur tremendous attention due to their unprecedented performance in photovoltaic applications. However, submicron thick perovskite films are prone to morphological defects in the form of cracks, pinholes and porosity; the traits originated from their solution phase processing and subsequent crystallization. Moreover, pinholes and cracks in the thin film of spincoated Spiro-OMeTAD hole transport layer reduce the performance reliability by forming micro shorts and weaken the defense against moisture ingress to the perovskite layer. For the large scale processing of perovskite solar cell from the economically prudent solution phase processing, morphological shortcomings of both perovskite and hole transport layers need an urgent address. By selecting non-conventional lead precursor (lead acetate) and implementing anti-solvent treatment during film deposition, we able to form pinhole free and compact perovskite film. Crack free hole conducting layer is obtained by blending Spiro-OMeTAD with a conducting polymer without compromising in the solar cell performance. A detail investigation of the charge transport and charge extraction properties of the developed hole transport layers have been carried out. The developed CH3NH3PbI3 based perovskite solar cells show improved repeatability and performance.

Reduction of trap and polydispersity in mutually passivated quantum dot solar cells - Sharma, Ashish; Mahajan, Chandan; Rath, Arup K. (ACS Applied Energy Materials, 2020)
Control over surface passivation is a key to manage the optoelectronic properties in low-dimensional nanomaterials because of their high surface-to-volume ratios. Tunable band gap quantum dots (QDs) are a potential building block for the development of optoelectronic devices like solar cells, photodetectors, and light-emitting diodes. Long and insulating surface ligands of colloidally synthesized QDs are exchanged by short ligands to attain compact arrangement in thin films to facilitate the charge transport process. However, the ligand exchange process often resulted in reduced surface passivation, inhomogeneous QD fusion, and deterioration of energy band gap, which adversely impact their performance in solar cells. Here, we introduce a surface passivation strategy where the QDs are mutually passivated by the organic ligand 3-methyl mercapto propionate and inorganic halometallate ligands to develop a conducting QD ink. The mutually passivated QDs (MPQDs) show significant improvement in optoelectronic properties in maintaining the trap-free energy band gap and size monodispersity. The photovoltaic performance of MPQDs shows a 33% average increase in power conversion efficiency (PCE) over the conventional halometallate passivation to attain 9.6% PCE in MPQD solar cells. The improvements in photovoltaic parameters are corroborated by the reduction in density of the intermediate trap states and an increase in depletion width and diffusion length in MPQD-based solar cells.
Keywords: polydispersity; quantum dot; solar cells; surface passivation; trap states

Solution-phase hybrid passivation for efficient infrared-band gap quantum dot solar cells - Mahajan, Chandan; Sharma, Ashish; Rath, Arup K. (ACS Applied Materials & Interfaces, 2020)
The broad tunability of the energy band gap through size control makes colloidal quantum dots (QDs) promising for the development of photovoltaic devices. Large-size lead sulfide (PbS) QDs, exhibiting a narrow energy band gap, are particularly interesting as they can be used to augment perovskite and c-Si solar cells due to their complementary NIR absorption. However, their complex surface chemistry makes them difficult to process for the development of solar cells. The shape of the QDs transformed from octahedron to cuboctahedron as their size increases, a phenomenon guided by surface energy minimization. As a result, the surface properties change drastically for large-size QDs, which exhibit nonpolar (200) facets and polar (111) facets, as opposed to only (111) facets in small-size QDs. Recent advancements in solution-phase surface passivation strategies, used for the development of high-performance solar cells using the small size and wide band gap QDs, failed to translate a similar enhancement in the case of large-size and narrow band gap QDs. Here, we report a hybrid passivation strategy for large-size and narrow band gap QDs to passivate both (111) and (200) facets, respectively, using inorganic lead triiodide (PbI3-) and organic 3-chloro-1-propanethiol (CPT). By employing charge balance calculation, we identified the desired narrow band gap for QDs to complement the perovskite and c-Si absorption. The distinct choice of the organic ligand CPT enhances the colloidal stability of QDs in the solution phase and improves surface passivation to stop QD fusion in solid films. Photophysical properties show narrower excitonic and emission peaks and a reduction in the Stokes shift. Hybrid passivation leads to a 94% increase in the power conversion efficiency of solar cells and a 74% increase in the external quantum efficiency at the excitonic peak.
Keywords: infrared band gap; polydispersity; quantum dot; solar cells; surface passivation; trap states

Crack-free conjugated PbS quantum dot-hole transport layers for solar cells - Sharma, Ashish; Dambhare, V. Neha; Bera, Jayanta; Sahu, Satyajit; Rath, Arup K. (ACS Applied Nano Materials, 2021)
Colloidal quantum dots (QDs) benefit from solution-phase processing and band-gap tuning for their application in solar cell development. Today's QD solar cells rely on solid-state ligand exchange (SLE) to replace bulky oleic acid (OA) ligands with small 1,2-ethanedithiol (EDT) ligands to develop a conducting hole transport layer (HTL). High volume contraction in EDT conjugated QD films, however, leads to crack and porosity in the HTL, which is a major cause of concern for the device reproducibility and large-area solar cell development. We show that partial removal of the OA ligands in the solution phase reduces the volume contraction in solid films, thereby allowing the growth of crack-free QD films in the SLE process. The cleaning of QDs by repeated precipitation and redispersion using a protic methanol (MeOH) solvent helps with partial removal of the OA ligands, but it is detrimental to the electronic properties of QDs. We develop a one-step solution-phase partial ligand-exchange process using ammonium salts, which enable partial replacement of the OA ligands and passivation of the QD surface. Introduction of the facile partial ligand-exchange process eliminates the need for tedious and wasteful multiple cleaning steps with MeOH, while improving the photophysical properties of QDs. The advancement in QD processing helps to build crack-free, smooth, and conjugated QD films for their deployment as HTLs in solar cell development. Partial ligand exchange with NH4SCN leads to a 1.5 times increase in p doping and mobility over multiple MeOH-cleaned PbS QD films. HTLs developed using NH4SCN QDs show an improved photovoltaic performance to attain a 10.5% power conversion efficiency. Improvement in the depletion width and hole collection efficiency leads to a superior photovoltaic performance, as confirmed from experimental studies and one-dimensional solar cell capacitance simulation.
Keywords: Efficiency; ligand; polydispersity; quantum dot; solar cells; thin film

CdSe quantum dot-based nanocomposites for ultralow-power memristors - Bera, Jayanta; Betal, Atanu; Sharma, Ashish; Shankar, Uday; Rath, Arup Kumar; Sahu, Satyajit (ACS Applied Nano Materials, 2022)
The explosion in digital communication with the huge amount of data and the internet of things (IoT) led to the increasing demand for data storage technology with faster operation speed, high-density stacking, nonvolatility, and low power consumption for saving energy. Metal chalcogenide-based quantum dots (QDs) show excellent nonvolatile resistive memory behavior owing to their tunable electronic states and control in trap states by passivating the surface with different ligands. Here, we synthesized high-quality colloidal monodispersed CdSe QDs by the hot injection method. The CdSe QDs were blended with an organic polymer, poly(4-vinylpyridine) (PVP), to fabricate an Al\textbackslashCdSe-PVP\textbackslashAl device. Our device shows excellent bipolar nonvolatile resistive random access memory (RRAM) switching behavior with a high current ON/OFF ratio (I-ON/OFF) of 6.1 x 10(4), and it consumes ultralow power. The charge trapping and detrapping in the potential well formed by the CdSe QD and PVP combination result in resistive switching. This CdSe-PVP-based resistive random access memory (RRAM) device with a high I-ON/OFF, ultrafast switching speed, high endurance, low operating voltage, and long retention period can be used as a high-performance and ultralow-power memristive device.
Keywords: memory switching; memristor; metal chalcogenides; nonvolatile; quantum dots

Colloidal MoS2 quantum dots for high-performance low power resistive memory devices with excellent temperature stability - Bera, Jayanta; Betal, Atanu; Sharma, Ashish; Rath, Arup Kumar; Sahu, Satyajit (Applied Physics Letters, 2022)
Conventional memory technologies are facing enormous problems with downscaling, and are hence unable to fulfill the requirement of big data storage generated by a huge explosion of digital information. A resistive random access memory device (RRAM) is one of the most emerging technologies for next-generation computing data storage owing to its high-density stacking, ultrafast switching speed, high non-volatility, multilevel data storage, low power consumption, and simple device structure. In this work, colloidal MoS2 quantum dots (QDs) embedded in an insulating matrix of poly-(4vinylpyridine) (PVP) were used as an active layer to fabricate a RRAM device. The MoS2 QDs-PVP based RRAM device reveals an excellent nonvolatile resistive switching (RS) behavior with a maximum current on-off ratio (I-ON/I-OFF) of 10(5). High endurance, long retention time, and successive ``write-read-erase-read'' cycles indicate high-performance RRAM characteristics. The ultimate power consumption by this RRAM device is considerably low for energy saving. In addition, the MoS2 QDs-PVP based device shows RS behavior even at 130 degrees C. High I-ON/I-OFF, low operating power, high endurance, long retention time, and excellent stability with temperatures reveal that the MoS2 QDs-PVP based device can be a promising candidate for high-performance low power RRAM devices that can be operated at relatively higher temperatures. Published under an exclusive license by AIP Publishing.

Composition and surface morphology invariant high on-off ratio from an organic memristor - Betal, Atanu; Bera, Jayanta; Sharma, Ashish; Rath, Arup K.; Sahu, Satyajit (ACS Applied Electronic Materials, 2022)
Material composition plays a crucial role in the device performance; thus, nonvolatile memory devices from a small molecule named 5-mercapto-1-methyl tetrazole (MMT) in an insulating polymer matrix of poly(4-vinyl pyridine) (PVP) were fabricated. The composition of the active material in the device was varied to observe its influence on the device's electronic properties. The device with a more or less weight ratio of MMT has a much smoother surface morphology, whereas when the contributions of MMT and PVP were equal, the average surface roughness increased. However, the maximum on-off current ratio for all the devices is 10(5), suggesting that the MMT molecule does not show any change in its characteristic properties when surrounded by an insulating material. When the device was fabricated without the polymer matrix, the surface morphology of the device completely changed as it was filled with large holes. These holes provide short-circuited pathways for the current by forming the direct metal contact between the top and bottom electrodes. The carrier transport through these devices follows various conduction mechanisms. Some of the dominating conduction mechanisms are direct tunneling and trap-free and trap-assisted space-charge-limited conduction.
Keywords: Nonvolatile memory; Polymer; small molecule; space-charge; tunneling

Thiocyanate- and thiol-functionalized p-doped quantum dot colloids for the development of bulk homojunction solar cells - Dambhare, V. Neha; Sharma, Ashish; Mahajan, Chandan; Rath, Arup K. (Energy Technology, 2022)
Progress in device engineering and surface passivation strategies has led to steady progress in colloidal quantum dot (QD) solar cells. Bulk homojunction (BHJ) device architecture has several advantages over the conventional planar junction in developing QD solar cells. Herein, surface ligand chemistry is utilized to control the doping type and dispersibility of oppositely doped PbS QDs to develop BHJ solar cells. Thiocyanate and thiol ligand combination is introduced to develop p-PbS QD ink, which is blended with halide-passivated n-PbS QDs to build BHJ solar cells. It is shown that BHJ solar cells are benefited from high energy offset and higher hole mobility. This leads to the superior carrier extraction from a thicker active layer without compromising fill factor and open circuit voltage. Power conversion efficiency has reached 10.7% in 530 nm-thick BHJ solar cells, a 24% improvement over the best performing planar solar cells. With the help of the 1D solar cell capacitance simulator, it is shown that a 15% efficient QD solar cell can be realized by further improving the hole mobility above 0.1 cm(2) V-1 s(-1).
Keywords: bulk homojunctions; Doping; quantum dots; solar cells; surface functionalization

Charge trapped CdS quantum dot embedded polymer matrix for a high speed and low power memristor - Betal, Atanu; Bera, Jayanta; Sharma, Ashish; Rath, Arup K. K.; Sahu, Satyajit (Physical Chemistry Chemical Physics, 2023)
The data storage requirement in the digital world is increasing day by day with the advancement of the internet of things. In this respect, nonvolatile resistive random-access memory is an option that provides high density and low power data storage capabilities. In this work, zero-dimensional colloidal CdS quantum dots and a polymer composite at an appropriate ratio were used to fabricate a memristive device. Comparison with a pristine CdS quantum dot-based device reveals that a surrounding matrix around the quantum dots is needed for observing memristive behavior. The quantum dots embedded in the polymer matrix device showed extremely stable electrical switching behavior that can be operated for more than 300 cycles and 60 000 seconds. Moreover, the device needs extremely low power to operate at a very high speed. The smooth surface morphology dictates a charge trapping mechanism for the switching phenomenon; however, an interplay between different charge transport mechanisms leads to the fast switching and high on-off ratio of the device.

Scanning tunneling microscopy investigation of synaptic behavior in AgInS2 quantum dots: effect of ion transport in neuromorphic applications - Betal, Atanu; Chetia, Anupam; Bera, Jayanta; Saikia, Dibyajyoti; Sharma, Ashish; Rath, Arup K.; Sahu, Satyajit (ACS Applied Nano Materials, 2024)
Scanning tunneling microscopy (STM) is a powerful technique for investigating the nanoscale properties of functional materials. Additionally, scanning tunneling spectroscopy (STS) facilitates the determination of the local density of states (LDOS) within the material. In this study, we present an exploration of the resistive switching (RS) properties and neuromorphic computing capabilities of individual AgInS2 quantum dots, utilizing STM and STS techniques. By examining the material's bandgap and its temperature dependence, we uncover a nonlinear variation below the Debye temperature and a linear trend at higher temperatures. Moreover, STS measurements demonstrate changes in the conducting states induced by localized pulses, further confirming the unique characteristics of the quantum dots. The experimental devices constructed by using these quantum dots effectively replicate the RS properties observed at the nanoscale. To assess the neuromorphic application of the devices, pulse transient measurements simulating the learning and forgetting processes were conducted. The gradual set and reset processes successfully mimic the information retention and erasure capabilities essential for neuromorphic computing. Notably, the resistive switching mechanism in these devices is attributed to localized ionic transport, which highlights the significant involvement of ionic species in the observed RS behavior. The outcomes of this study contribute to the fundamental understanding of RS properties in single AgInS2 quantum dots and offer valuable insights into their potential applications in neuromorphic computing.
Keywords: corona poling; Ion transport; neuromorphic computing; quantum dots; resistive switching; Scanning tunneling microscopy; STS

Solution-phase ligand engineering for all-quantum-dot near-infrared light-emitting diodes - Biswas, Arindam; Mitra, Anurag; Sharma, Ashish; Shinde, Dipak Dattatray; Dambhare, V. Neha; Sharma, Anjali; Mahajan, Chandan; Rath, Arup K. (ACS Applied Nano Materials, 2024)
Strong emission over a wide near-infrared (NIR) region makes lead sulfide quantum dots (QDs) a preferred material in building NIR light-emitting diodes (NIR-LEDs) for numerous applications. Narrow-bandgap emitter QDs blended in the matrix of high-band gap QDs offer a simple yet powerful architectural platform for building high-performance NIR-LEDs. So far, the all-QD-based blend architecture has been realized using a poorly controlled solid-state ligand exchange approach. Advanced solution-phase ligand exchange, which offers greater control over surface passivation, is yet to be realized in all-QD LED device construction. We observe that the solution-phase ligand exchange from the optimized lead halide and thiol ligand combination, used in high-performing QD solar cell construction, is inefficient in realizing efficient all-QD LEDs, which could have restricted the adoption of the solution-phase ligand exchange thus far. Here, we introduce an innovative dual-ligand strategy to build all-QD-based NIR-LEDs using an advanced solution-phase ligand exchange approach. Through ligand engineering of matrix QDs, we managed to improve photoluminescence quantum yield (40%), reduce trap density (10(14) cm(-3)), and prolong carrier lifetime (832 ns). The LED devices benefit from improved electronic properties and balanced carrier injection to yield 6% EQE and 7.7% PCE, which are six times higher than those of state-of-the-art ligands.
Keywords: electroluminescence; lead sulfide; ligand passivation; light-emitting diodes; near-infrared; quantumdots